TCP/IP-based control and monitoring of manufacturing system - Abrishamkar, M. (Trans Tech Publication, 2014)
In this paper, a framework for remote monitoring and controlling of manufacturing system at lower level of automation in manufacturing is proposed. This framework has capability to develop the higher level of automation in manufacturing. In order to proof that the proposed framework can be implemented, a demo system based on the framework is built.Computer-Integrated Manufacturing (CIM) system as a manufacturing system is controlled and monitored remotely within demo system was utilised. In general, the system consists of two Graphical User Interface (GUI) program; one as a client and the other one as server program connected using TCP/IP protocol. The system proposed include the CIM system which connected to the server computer and able to controlled and monitored via the client GUI program. In addition for demonstration purposes, several sub-systems of the CIM system which includes the conveyor, stoppers, sensors and the pick and place robot were used to control and monitor the system development. The programming language used in this system is Visual C++ with Microsoft Foundation Class (MFC) application. The overall developed system has successfully demonstrates the ability of remotely control the system.